Ganaxolone: A New Treatment for Neonatal Seizures - Yawno, Tamara; Miller, Suzie L.; Bennet, Laura; Wong, Flora; Hirst, Jonathan J.; Fahey, Michael; Walker, David W. (Frontiers in Cellular Neuroscience, 2017)
Neonatal seizures are amongst the most common neurologic conditions managed by a neonatal care service. Seizures can exacerbate existing brain injury, induce ‘de novo’ injury, and are associated with neurodevelopmental disabilities in post-neonatal life. In this mini-review, we present evidence in support of the use of ganaxolone, a GABAA agonist neurosteroid, as a novel neonatal therapy. We discuss evidence that ganaxolone can provide both seizure control and neuroprotection with a high safety profile when administered early following birth-related hypoxia, and show evidence that it is likely to prevent or reduce the incidence of the enduring disabilities associated with preterm birth, cerebral palsy, and epilepsy. We suggest that ganaxolone is an ideal anti-seizure treatment because it can be safely used prospectively, with minimal or no adverse effects on the neonatal brain.